Space exploration throughout history : from telescopes to tourism - Lombardo, Jennifer (World history (Lucent Press), 2020)
Describes the exploration of space from ancient times to the present, discussing notable scientists, space missions, and developments. Also discusses the future of space exploration. Includes a timeline, photographs, primary sources, and further resources.